'A New Order of Things': Benjamin Furly, Quakers and Quietism in the Seventeenth Century. Issue 2 (December 2018) - Pryce, Elaine
Abstract : The historian Paul Hazard commented that, 'In the closing years of the seventeenth-century a new order of things began its course.'1 This article examines Quaker connections with Quietism in the theological and cultural context of the later seventeenth century, as reflected and contextualised in the diverse social milieux of Benjamin Furly's Quaker home and wider friendship network. It contends that through Furly, his alliances and the creation of his library, as well as the querulous times they lived in, Quietists were understood by Quakers as innovators and as belonging to the forward-thinking new order of early Enlightenment principles of spiritual democracies, toleration and liberty of conscience.